Teaching of the theme "humanization of care" in undergraduate nursing courses at state universities in Paraná - Ferraz, Marcela Aparecida Alvarez; Azarias, Késsia G. B.; Waner, Carolina Godoy; dos Santos, Maria E. Caetano; Giordani, Annecy T.; B., Tatiane A. Phelipini (Seven Editora, 2024)
Introduction: The National Curriculum Guidelines for undergraduate nursing courses frequently propose reforms in the curricula of higher education institutions whenever changes are needed to create new demands and updates relevant to quality professional training. However, it seeks to break with the mere fulfillment of professional practice to incorporate teaching focused on the real needs of society and the world of work. Enabling the training of professionals with a holistic view of user care in accordance with the National Humanization Policy. Objective: To analyze how the theme "Humanization of Care" is proposed in the Pedagogical Course Projects (PPC) of the Undergraduate Nursing courses of the State Universities of Paraná. Methodology: A documentary analysis research was carried out, with the aim of constituting a satisfactory corpus, exhausting the clues capable of providing relevant information in relation to the theme. Document analysis is a set of intellectual operations that aims at the description and representation of documents in a unified and systematic way to facilitate their retrieval extracted from the original source, allowing the location, organization and evaluation of the information contained. Finally, the collected data were organized in Excel spreadsheets separated by tabs, in order to gather the most relevant data in a concise and objective way so that the findings and results pertinent to the research objective can be later discussed. Result: The Document Analysis allowed the deepening of the theme of Teaching Humanization due to its characteristic of constituting a satisfactory corpus, exhausting all clues capable of providing relevant information in relation to the theme. Thus, by effectively integrating politics as a basis for teaching, an environment is created that favors the development of a professional with a more humane, ethical and integrated vision with both the needs of patients and the health team. Conclusion: However, in order to have professionals with knowledge about the Humanization of Care and to be able to actually provide humanized care and assistance, it is essential that during their training they have come into contact with the theme in a theoretical-practical way, and that this contact happens throughout the undergraduate course.  In this sense, contributing to the development and improvement of nursing education, and promoting reflections on the insertion of Humanization in the education of future nurses in a substantial way, is justified by the fact that humanized practice contemplates the individual in a holistic way, promoting prevention, promotion, and treatment. DOI:https://doi.org/10.56238/sevened2024.026-041